Coronavirus virus disease (COVID-19) outbreak south-east Asia [electronic resource] - World Health Organization. Regional Office for South-East Asia. (New Delhi, India World Health Organization, Regional Office for South-East Asia, 2020)
COVID-19 is an emerging, rapidly evolving situation. Get the latest public health information from this site.
mixed.
online.
Keywords: Electronic information resources; Internet research; Internet in higher education; Open learning; Open education; Open access publishing; Education, Higher; COVID-19 (Disease) -- Research -- Electronic information resources; COVID-19 (Disease) -- South-east Asia -- Electronic information resources; Open access publishing; South-east Asia -- COVID-19 (Disease) -- Electronic information resources; Bangladesh -- COVID-19 (Disease) -- Electronic information resources; Bhutan -- COVID-19 (Disease) -- Electronic information resources; Democratic People's Republic of Korea -- COVID-19 (Disease) -- Electronic information resources; India -- COVID-19 (Disease) -- Electronic information resources; Indonesia -- COVID-19 (Disease) -- Electronic information resources; Maldives -- COVID-19 (Disease) -- Electronic information resources; Myanmar -- COVID-19 (Disease) -- Electronic information resources; Nepal -- COVID-19 (Disease) -- Electronic information resources; Sri Lanka -- COVID-19 (Disease) -- Electronic information resources; Thailand -- COVID-19 (Disease) -- Electronic information resources; Timor-Leste -- COVID-19 (Disease) -- Electronic information resources